Anatomy and clinical relevance of sub occipital soft tissue connections with the dura mater in the upper cervical spine - Rob Sillevis; Russell Hogg (PeerJ, 2020)
Background The upper cervical region is a complex anatomical structure. Myodural bridges between posterior suboccipital muscles and the dura might be important explaining conditions associated with the upper cervical spine dysfunction such as cervicogenic headache. This cadaver study explored the upper cervical spine and evaluated the myodural bridges along with position of spinal cord in response to passive motion of upper cervical spine. Methods A total of seven adult cadavers were used in this exploratory study. The suboccipital muscles and nuchal ligament were exposed. Connections between the Rectus Capitis Posterior major/minor and the Obliquus Capitis minor, the nuchal ligament, posterior aspect of the cervical spine, flavum ligament and the dura were explored and confirmed with histology. The position of the spinal cord was evaluated with passive motions of the upper cervical spine. Outcomes In all cadavers connective tissues attaching the Rectus Capitis Posterior Major to the posterior atlanto-occipital membrane were identified. In the sagittal dissection we observed connection between the nuchal ligament and the dura. Histology revealed that the connection is collagenous in nature. The spinal cord moves within the spinal canal during passive movement. Discussion The presence of tissue connections between ligament, bone and muscles in the suboccipital region was confirmed. The nuchal ligament was continuous with the menigiovertebral ligament and the dura. Passive upper cervical motion results in spinal cord motion within the canal and possible tensioning of nerve and ligamentous connections.